2004
DOI: 10.1385/bter:100:3:259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lead Ions on Rat Erythrocyte Purine Content

Abstract: The influence of short-term exposure to lead on the energetic status of erythrocytes in rats is reported in this study. The male Wistar rats selected for this study drank water containing 1% lead(II) acetate and/or intraperitoneal injections of 1 or 2 mg/kg body wt every 4 d starting on the eighth of the experiment, over a period of 1 mo. The whole-blood lead concentration measured after 4 wk was 1.51-35.31 microg/dL. The concentrations of adenosine, adenosine triphosphates, diphosphates, and monophosphates (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The concentrations of purine metabolites depend on the unique functions of each cell type (erythrocytes, lymphocytes, liver) and even on the developmental phase of the cells (Traut, 1994 ). In erythrocytes from humans and rats, purine nucleotides cannot be synthesized de novo , and can only be reconstructed from pre-existing free purine bases or nucleosides (Baranowska-Bosiacka and Hlynczak, 2004 ), which can contribute to explain the lower concentrations of HX and higher concentrations of purine nucleosides and nucleotides in erythrocytes of all three species analyzed in this study. The higher concentration of HX in heart and kidney of domestic pigs, as compared to ringed seals, after experimental ischemia, suggests an increase of ATP degradation in domestic pigs (Elsner et al, 1998 ).…”
Section: Discussionmentioning
confidence: 96%
“…The concentrations of purine metabolites depend on the unique functions of each cell type (erythrocytes, lymphocytes, liver) and even on the developmental phase of the cells (Traut, 1994 ). In erythrocytes from humans and rats, purine nucleotides cannot be synthesized de novo , and can only be reconstructed from pre-existing free purine bases or nucleosides (Baranowska-Bosiacka and Hlynczak, 2004 ), which can contribute to explain the lower concentrations of HX and higher concentrations of purine nucleosides and nucleotides in erythrocytes of all three species analyzed in this study. The higher concentration of HX in heart and kidney of domestic pigs, as compared to ringed seals, after experimental ischemia, suggests an increase of ATP degradation in domestic pigs (Elsner et al, 1998 ).…”
Section: Discussionmentioning
confidence: 96%
“…Very interestingly, changes in these cellular levels are actually discussed to serve as sensitive biomarkers for environmental exposure towards toxic compounds. Thus, they might also be suitable biomarkers for acute or chronic metal(loid) exposure, which has been tested recently for lead, [19][20][21][22] zinc 23 and cadmium. 24 For other metal(loid) compounds, including manganese and arsenic species, some hints exist, indicating that these metal(loid) species affect the cellular level of single adenine and/or pyridine nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…Untargeted metabolomics analysis showed that a host of nucleotides and intermediates in purine metabolism were negatively correlated with the synthesis rate of γ-PGA, which was consistent with the results of Halmschlag et al 27 Bacillus subtilis can degrade nucleotides into corresponding bases and 1-phosphate ribose, and 1-phosphate ribose can be converted into ribose-5-P, which flows into the glycolytic pathway and promotes the production of γ-PGA. 40,41 A lot of complex metabolic pathways may compete for carbon sources and disperse carbon fluxes. 23 Therefore, it is speculated that the higher demand for carbon flux for the synthesis of glutamic acid by glycolysis to the TCA cycle leads to a decrease in the concentration of intermediate products of anthocyanin biosynthesis and isoflavonoid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%